Breakpoint analysis of IKZF1 gene deletions in patients with B-cell precursor acute lymphoblastic leukemia - Keraz, Maryia A.; Bogatenkova, Darya A.; Vshyukova, Volha S.; Meleshko, Alexander N. (Experimental Biology and Biotechnology, 2024)
In addition to the long-known diagnostically significant rearrangements in B-cell precursor acute lymphoblastic leukemia, such as BCR::ABL1, TCF3::PBX1 (E2A::PBX1) and KMT2A (MLL), mutations in genes of transcription factors, which controls lymphoid differentiation, primarily mutations in the IKZF1 gene, are of considerable interest in predicting the course of the disease. The IKZF1 gene encodes a DNA-binding protein Ikaros, which is a key transcription factor that regulates early steps in the differentiation of T- and B-lymphocytes, NK cells and dendritic cells. In B-cell precursor acute lymphoblastic leukemia, the most common genetic events involving the IKZF1 gene are intragenic deletions that result in the loss of several exons. These deletions are observed in pediatric and adult patients with B-cell precursor acute lymphoblastic leukemia, with a higher prevalence in cases where there is a BCR::ABL1 translocation. There are also known splicing disorders expressed in increased expression of short IKZF1 gene transcripts (isoforms). However, in the vast majority of cases, increased expression of short isoforms is a consequence of intragenic deletion. These molecular genetic changes contribute to the dysregulation of lymphoid differentiation and are associated with a poor prognosis for patients with B-cell precursor acute lymphoblastic leukemia. Understanding the genetic alterations in key transcription factors, such as Ikaros, can provide valuable insights into the biology of B-cell precursor acute lymphoblastic leukemia and help in predicting the clinical outcomes of patients with this disease.